2017
DOI: 10.1007/s00411-017-0709-2
|View full text |Cite
|
Sign up to set email alerts
|

How radiation influences atherosclerotic plaque development: a biophysical approach in ApoE ¯/¯ mice

Abstract: Atherosclerosis is the development of lipid-laden plaques in arteries and is nowadays considered as an inflammatory disease. It has been shown that high doses of ionizing radiation, as used in radiotherapy, can increase the risk of development or progression of atherosclerosis. To elucidate the effects of radiation on atherosclerosis, we propose a mathematical model to describe radiation-promoted plaque development. This model distinguishes itself from other models by combining plaque initiation and plaque gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The radiation field for OCC is in the proximity of the carotid arteries, and the effect of ionizing radiation on plaque formation has been reported [10]. Despite the introduction of intensity-modulated RT in Taiwan, the late effects of radiation resulting in vascular injury are inevitable due to radiation scattering.…”
Section: Discussionmentioning
confidence: 99%
“…The radiation field for OCC is in the proximity of the carotid arteries, and the effect of ionizing radiation on plaque formation has been reported [10]. Despite the introduction of intensity-modulated RT in Taiwan, the late effects of radiation resulting in vascular injury are inevitable due to radiation scattering.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of ionizing radiation on atherosclerosis has been previously reported . Radiation has a role in promoting plaque initiation and dose‐related effects on plaque growth . Despite the advent of intensity‐modulated radiotherapy , the late effects of radiation resulting in vascular injury are inevitable from the viewpoint of radiation scattering.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Experimental studies have shown both sparing and enhancing (inverse) dose protraction effects of radiation exposure on the circulatory system [23][24][25][26][27][28][29] , and consensus has not yet been reached regarding dose rate effectiveness 30,31 . Recently Kloosterman and colleagues 32 have developed a biophysical mathematical model to describe the radiation-promoted atheroslerotic plague development. The authors state that with the adequate experimental data available this model could be further elaborated to take into account the dose rate effect.…”
Section: Tablementioning
confidence: 99%